Capacity planning in in-plant milk run system. (1st January 2014) - Alnahhal, Mohammed; Noche, Bernd
This study investigates material flow in in-plant milk run system in which a tugger train transports materials and parts from a warehouse to several workstations in one route. The focus of the paper is to deal with train capacity problems due to the dynamic nature of workstations demand where several unique product models needing unique demand requirements are assembled. Dynamic train cycle time, early loading, and minimising extra number of trailers are the tools used in this study to minimise the needed train capacity keeping the area beside stations not to be crowded with bins more than its capacity. This is done step by step using four integer programming models. Randomly generated instances showed that combining the three tools results in great decrease for the extra needed number of trailers, but small decrease in the maximum needed number of trailers.